2007
DOI: 10.1073/pnas.0700332104
|View full text |Cite
|
Sign up to set email alerts
|

A connecting hinge represses the activity of endothelial nitric oxide synthase

Abstract: In mammals, endothelial nitric oxide synthase (eNOS) has the weakest activity, being one-tenth and one-sixth as active as the inducible NOS (iNOS) and the neuronal NOS (nNOS), respectively. The basis for this weak activity is unclear. We hypothesized that a hinge element that connects the FMN module in the reductase domain but is shorter and of unique composition in eNOS may be involved. To test this hypothesis, we generated an eNOS chimera that contained the nNOS hinge and two mutants that either eliminated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 52 publications
3
98
0
Order By: Relevance
“…from the heme is the transfer of electrons from the reductase domain to the oxygenase domain (47,48), which in the global kinetic model of NOS activity proposed by Stuehr et al (49) is the same rate-limiting step for NO production. Thus, it would be expected that any modification that alters eNOS NO production will similarly alter the activity of the uncoupled enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…from the heme is the transfer of electrons from the reductase domain to the oxygenase domain (47,48), which in the global kinetic model of NOS activity proposed by Stuehr et al (49) is the same rate-limiting step for NO production. Thus, it would be expected that any modification that alters eNOS NO production will similarly alter the activity of the uncoupled enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the prior work using S1177D and ⌬27, our data support this hypothesis. However, although Ser-1177 phosphorylation enhances the eNOS-CaM interaction, this phosphorylation event also would lead to an increase in the absolute rate of electron transfer from the reductase domain to the heme with increased flavin reduction rate, a hallmark of AR inhibition release (47).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the 42 residue-long eNOS C-terminal tail most likely contributes to eNOS having the weakest activity among three NOSs. One other factor contributing to the slow activity of eNOS has been shown to be the linker between the two flavin domains (61).…”
Section: The Structure Of the Inos Reductase Domain In The Closed Andmentioning
confidence: 99%
“…tase activity than nNOS (15,16). The basis for these differences is unclear, but it appears to involve slower electron transfer by eNOSr.…”
mentioning
confidence: 93%
“…Previous studies have investigated structural elements that appear to regulate NOS activity. These include an autoinhibitory element in the FMN binding subdomain (a 40 -50-amino acid loop) (17)(18)(19), a connecting hinge domain between the FMN and FAD binding subdomains (23-25-amino acid residues) (15,20), and the C-terminal tail (21-42-amino acid extension) (16,21,22). It has also been shown that an FAD stacking residue (Phe-1160 in bovine eNOS and Phe-1395 in rat nNOS) and site-specific phosphorylation (Ser-1179 in bovine eNOS and Ser-1412 in rat nNOS) are involved in the catalytic regulation of NOS enzymes (21,(23)(24)(25).…”
mentioning
confidence: 99%